2-(Nitroaryl)benzothiazole and benzoxazole derivatives as fluorogenic substrates for the detection of nitroreductase activity in clinically important microorganisms. Issue 24 (15th December 2015) - Cellier, Marie; Gignoux, Amandine; James, Arthur L.; Orenga, Sylvain; Perry, John D.; Robinson, Shaun N.; Stanforth, Stephen P.; Turnbull, Graeme
Graphical abstract: Abstract: A series of carboxy-substituted 2-(nitroaryl)benzothiazole derivatives and carboxy-substituted 2-(nitroaryl)benzoxazole derivatives were prepared and evaluated as potential nitroreductase substrates for the purpose of detecting clinically important microorganisms. Several of the substrates produced highly fluorescent colonies with the majority of a panel of 10 Gram-negative bacteria and also with two of a panel of 8 Gram-positive bacteria.